Post Truth Dalam Perseteruan Indonesia-Uni Eropa Mengenai Isu Kelapa Sawit [Post Truth in Indonesia-European Union Dispute Over Palm Oil Issue] - Aditya Dwinda Pratama (Sekretariat Jenderal DPR RI, 2019)
The dispute between the European Union (EU) and Indonesia over palm oil issue was triggered by the EU boycott of palm oil commodities. Indonesia as the largest producer of palm oil certainly feels disadvantaged by the EU's stance because it lost the market. The EU boycotted oil palm because it was not in line with its commitments on Sustainable Development Goals (SDGs) which focus on the environment. Palm oil is considered as a commodity that causes a lot of environmental damages. Indonesia challenged the EU at the World Trade Center (WTO) due to EU’s discrimination against the trade of palm oil in the European market. Indonesia also questioned EU's commitment to the SDGs with regard to poverty eradication, which Indonesia was working on. The dispute between the two parties in their defense has left questions about the truth behind their standpoints. As the world embarks into the age of post-truth, critical thinking is required to analyze the truth of an issue. This paper is made to question the truth of the defense carried out by the EU and Indonesia so that people are able to take a stand on what they believe is true. The truth is too often determined by the most massive information reported by the media, so to analyze the issues in this paper the author uses literacy observation method, especially through observations of the news in the media related to this issue. To analyze the real truth about the dispute between Indonesia and the EU on the issue of palm oil, it is necessary to understand the post truth theory, trade-off theory and national theory so as to analyze all the interests behind EU and Indonesian policies. Being critical by exploring the reality behind a truth that has been constructed by the media that distributes information is an absolute necessity for every individual in the post truth era.AbstrakPerseteruan antara Uni Eropa (UE) dan Indonesia tentang kelapa sawit dipicu oleh pemboikotan UE terhadap komoditas kelapa sawit. Indonesia sebagai produsen terbesar kelapa sawit tentu merasa dirugikan oleh sikap UE tersebut karena kehilangan pasar. UE memboikot kelapa sawit karena tidak sesuai dengan komitmen UE dalam Sustainable Development Goals (SDGs) yang berfokus pada lingkungan. Kelapa sawit dinilai sebagai komoditas yang menimbulkan banyak kerusakan lingkungan. Indonesia menggugat perlakuan UE ke World Trade Centre (WTO) akibat diskriminasi UE terhadap kelapa sawit di pasar Eropa. Indonesia juga mempertanyakan komitmen UE terhadap SDGs yang seharusnya memperhatikan juga poin pemberantasan kemiskinan yang sedang diusahakan Indonesia. Perseteruan antara keduanya dengan pembelaan masing-masing menyisakan pertanyaan tentang kebenaran yang mereka bawa. Dunia yang masuk di era post truth memerlukan pemikiran yang kritis untuk menganalisa kebenaran akan suatu isu. Tulisan ini dibuat untuk mempertanyakan kembali kebenaran dari pembelaan yang dilakukan UE dan Indonesia sehingga masyarakat mampu menempati posisi yang benar-benar mereka inginkan. Kebenaran telah terlalu sering ditentukan oleh informasi yang paling masif diberitakan oleh media, sehingga untuk menganalisa isu pada tulisan ini penulis menggunakan pengamatan literasi, terutama mengamati berita-berita yang media distribusikan terkait isu ini. Untuk menganalisa kebenaran sesungguhnya tentang perseteruan Indonesia dan UE pada isu kelapa sawit perlu untuk memahami post truth theory, trade off theory, dan national theory sehingga mampu menganalisa segala kepentingan dibalik kebijakan UE dan Indonesia. Bersikap kritis dengan menggali kenyataan dibalik sebuah kebenaran yang telah terkontruksi oleh media yang mendistribusikan informasi adalah sebuah hal yang mutlak untuk dilakukan oleh setiap individu di era post truth.